2015
DOI: 10.5430/jnep.v5n4p58
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of maternity nurses regarding cord blood collection and stem cells: An educational intervention

Abstract: Background: Cord blood collection and stem cell research are the most important and controversial topics of science and technology today. Nurses need to understand stem cell research so they can enter the debate on this issue. Aim was to evaluate the effect of an educational intervention on maternity nurses' knowledge and attitude regarding cord blood collection and stem cells.Method: Quasi-experimental design (pre and post intervention) was utilized. A total sample of 53 staff nurses were recruited in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 19 publications
6
26
0
Order By: Relevance
“…Similarly, Walker et al, (2012) reported that obstetricians indicated a desire for more information on cord blood banking. Mohammed and El Sayed (2015) revealed that 98.8 % (n = 52) of nurses had not attended stem cells training courses, which is in compliance with our findings; where 76.0% of our participants had never attended training courses on stem cells. An overall moderate knowledge about the stem cells in the study was noted among more than half 140 (56%) of the participants.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, Walker et al, (2012) reported that obstetricians indicated a desire for more information on cord blood banking. Mohammed and El Sayed (2015) revealed that 98.8 % (n = 52) of nurses had not attended stem cells training courses, which is in compliance with our findings; where 76.0% of our participants had never attended training courses on stem cells. An overall moderate knowledge about the stem cells in the study was noted among more than half 140 (56%) of the participants.…”
Section: Discussionsupporting
confidence: 80%
“…An overall moderate knowledge about the stem cells in the study was noted among more than half 140 (56%) of the participants. In contrast, two other studies concerning maternity nurses reported that most maternity nurses had a low knowledge levels of stem cells and its uses Mohammed and El Sayed, 2015). In addition to the finding of recent study (Khalil and Sharshor, 2016) that assessed the Nurses' Knowledge about stem cells in paediatric Intensive Care Unit and paediatric Hematology Department in Tanta, Egypt and also reported that Nurses' Knowledge about stem cells is inadequate in 69 % of participants.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Papers regarding health care professionals’ knowledge, attitudes and practices pertaining to cord blood banking and donation were conducted in North America [ 49 ], the United Kingdom [ 27 , 46 ], Europe [ 43 , 47 ], North Africa [ 44 , 45 ] and Asia [ 50 , 51 ]. No studies were located within Australasia or South America.…”
Section: Resultsmentioning
confidence: 99%
“…A strong majority of students (89.3%) also expressed willingness to develop their knowledge of stem cells in addition to the knowledge imparted through their curriculum which indicates that they are not neglectful of the topic and are encouraged to know more about it. Khali also reported that 92% of the respondents desired to attain coherent education about stem cells in a study conducted in Egypt [13].…”
Section: Discussionmentioning
confidence: 99%